Low-Grade Uterine Epithelioid Hemangioendothelioma Presented as a Submucosal Leiomyoma during Labor - Anastasios V. Koutsopoulos; Efthimios Sivridis; Panagiotis Tsikouras; Vasileios Liberis; Georgia Karpathiou; Alexandra Giatromanolaki (Case Reports in Pathology)
With the exception of leiomyomas, soft tissue tumors of the uterine corpus are not common. This is particularly true for vascular neoplasms, with the epithelioid hemangioendothelioma being a curiosity; not more than twenty-two cases of malignant hemangioendotheliomas have been reported in the literature so far, all of which were high-grade hemangioendotheliomas (hemangiosarcomas). We present herewith a unique case of low-grade epithelioid hemangioendothelioma of the uterus in a pregnant woman aged 29 years. The clinical, histological, and immunohistochemical characteristics of this entity, together with its differential diagnosis, are discussed.